真珠タンパク質フィルムによる真珠の形成 - 加納, 哲; KANOH, Satoshi (三重大学, 2014)
application/pdf 申請者は真珠を輝かせているマトリックスタンパク質をアコヤガイ貝殻からフィルムとして分離した．これを「真珠タンパク質フィルム」と名付け，その機能を探り基礎データを得ることを目的とした．このフィルムをガラス板上に貼り付け，アコヤガイおよびマガキの外套膜と貝殻の間に挿入し３～６ヶ月間飼育した．アコヤガイに新たにマトリックスタンパク質層，稜柱層および異常形態の稜柱層が確認された．一方，マガキは異常なマトリックスタンパク質層が形成された．新生した各層は挿入されたこのフィルムを異物と認識し，保護のために結晶層を作り出したと考えることもできる．これらの結晶層を真珠形成に利用するにはさらなる検討を要する． The authors isolated the matrix protein that contributes luster to pearls as a film from the pearl oyster shell and pearl. We named it, the pearl protein film. This study aimed to obtain basic data for the application and development of the pearl industry. The samples attached the pearl protein film on a glass plate were inserted between the shell and the mantle of the pearl oyster and pacific oyster. These oysters were kept in pearl farm for 3-6 months. Matrix protein layer, prismatic layer and the abnormal prismatic layer were observed newly, in the pearl oyster shell. On the other hand, abnormal matrix protein layers were formed in the pacific oyster. When foreign protein film was inserted into pearl oyster and pacific oyster respectively, it could be considered that newly observed matrix protein layer, prismatic layer and the abnormal prismatic layer were generated for protection of each shellfish. Further investigations were required for the purpose of this study. 2012年度～2013年度科学研究費補助金(挑戦的萌芽研究)研究成果報告書 24658183 research report